The inn at Rose Harbor [compact disc, unabridged] : a novel - Macomber, Debbie (Macomber, Debbie. Rose Harbor Inn., 2012)
Jo Marie Rose opens the Rose Harbor Inn bed and breakfast in Cedar Cove in order to start a new life, but the inn and its first guests bring surprises into Jo's life.